Handbook of fourier transform Raman and infrared spectra of polymers - Kuptsov, A. H. (Elsevier, 1998)
A collection of infrared and Raman spectra of 500 natural and synthetic polymers of industrial importance is presented in this book. A large variety of compounds are included, starting with linear polyolefins and finishing with complex biopolymers and related compounds. The spectra were registered using Infrared Fourier Transform Spectrometers in the laboratory of the All-Russia Institute of Forensic Sciences. The IR and Raman spectra are presented together on the same sheet. The accompanying data include general and structure formulae, CAS register numbers, and sample preparation conditions.
Includes indexes.
Keywords: Polymers -- Spectra -- Handbooks, manuals, etc.; Fourier transform spectroscopy -- Handbooks, manuals, etc.; Raman spectroscopy -- Handbooks, manuals, etc.; Fourier transform infrared spectroscopy -- Handbooks, manuals, etc.; elektronické knihy; electronic books